2019
DOI: 10.1016/j.tws.2019.106373
|View full text |Cite
|
Sign up to set email alerts
|

On the development of shell buckling knockdown factors for imperfection sensitive conical shells under pure bending

Abstract: Thin-walled cylindrical shells are used as adapters between cylindrical shells of different diameters in launch-vehicle systems or as tailbooms in helicopters. A major loading scenario for cylindrical shells is bending. The buckling moment of these shells is very sensitive to imperfections (geometry, loading conditions) which results in a critical disagreement between theoretical and experimental results for axially loaded cylindrical shells. The design of these stability critical shells is based on classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…As the dimple exacerbates, the first limit point decreases to a minimum and then increases to a certain load, which corresponds to the limit point of a fully localized single-dimple mode in the post-buckling regime. These observations are in line with the single perturbation load approach studies by Wagner [44], where it is shown that the shell structures collapse at this lower load. Friedrich & Schröder [45] also reported a similar observation that the local buckling in a displacement-controlled study corresponds to the global buckling in a load-controlled analysis.…”
Section: Numerical Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…As the dimple exacerbates, the first limit point decreases to a minimum and then increases to a certain load, which corresponds to the limit point of a fully localized single-dimple mode in the post-buckling regime. These observations are in line with the single perturbation load approach studies by Wagner [44], where it is shown that the shell structures collapse at this lower load. Friedrich & Schröder [45] also reported a similar observation that the local buckling in a displacement-controlled study corresponds to the global buckling in a load-controlled analysis.…”
Section: Numerical Studiessupporting
confidence: 91%
“…In §2, the snaking sequence of the shell is traced using the modified Riks solver, but it is impossible experimentally to trace the fingers of the load–displacement graph. Hence, to match the experimental buckling and post-buckling response, a nonlinear analysis is performed using a Newton–Raphson solver with artificial damping in ABAQUS [44,49]. Using the inverse distance weighted interpolation method, the measured geometrical imperfection is incorporated into the FE mesh [48,50].…”
Section: Specimen Fabricationmentioning
confidence: 99%
“…15 Some more optimized finite-element methods have been further proposed to divide the mesh of complex shell structures accurately with cutouts, to ensure the high efficiency and precision for numerical simulation. 16,17 The protective shield is another type of typical spherical–cylindrical thin-walled shell structure, which is widely used in underwater vehicles. 18 The buckling and post-buckling behaviors of the unstiffened or stiffened spherical dome are regarded as a classic and challenging topic.…”
Section: Introductionmentioning
confidence: 99%
“…This method, however, is limited to these structures with small initial geometrical imperfections. In fact, buckling failure, usually caused by large displacement, is very sensitive to initial geometrical imperfections [38][39][40][41]. So the Clement's method could not predict the progressive buckling load for structures with large initial geometrical defects.…”
Section: Introductionmentioning
confidence: 99%